A systematic review on the youth's healthcare facilities determinants in Seri Iskandar / Muhammad Adib Hafizi Mohd Khiri and Mohamad Haizam Mohamed Saraf - Mohd Khiri, Muhammad Adib Hafizi; Mohamed Saraf, Mohamad Haizam (2023)
The determinants for healthcare facilities are related to a person's health status and income. As Seri Iskandar is the educational hub of Perak, most of the youth's income level in Seri Iskandar is not adequate to obtain healthcare services from private healthcare facilities. Although several studies have been developed to identify the determinants of the elderly group, disabled and general population towards healthcare facilities, youth with different lifestyles and environments between areas will create varied determinants. Hence, this study was set out to analyse the existing literature on the determinants in the perspectives of youth groups in Seri Iskandar. The PRISMA review method had resulted in five main determinants, they were healthcare services, duration for medical examination, medical cost, healthcare technology and healthcare facility distance. For further research, these five determinants could contribute to the development of a comprehensive development plan for holistic healthcare facilities.